Protein kinase Cγ negatively regulates the intrinsic excitability in zebrin-negative cerebellar Purkinje cells - Watanave, Masashi; Kawachi, Mika; Konno, Ayumu; Aoki, Ryo; Fukai, Yuuki; Matsuzaki, Yasunori; Kaneko, Ryosuke; Hirai, Hirokazu (Frontiers in Cellular Neuroscience, 2024)
Protein kinase C γ (PKCγ), a neuronal isoform present exclusively in the central nervous system, is most abundantly expressed in cerebellar Purkinje cells (PCs). Targeted deletion of PKCγ causes a climbing fiber synapse elimination in developing PCs and motor deficit. However, physiological roles of PKCγ in adult mouse PCs are little understood. In this study, we aimed to unravel the roles of PKCγ in mature mouse PCs by deleting PKCγ from adult mouse PCs of PKCγ fl/fl mice via cerebellar injection of adeno-associated virus (AAV) vectors expressing Cre recombinase under the control of the PC-specific L7-6 promoter. Whole cell patch-clamp recording of PCs showed higher intrinsic excitability in PCs virally lacking PKCγ [PKCγ-conditional knockout (PKCγ-cKO) PCs] than in wild-type (WT) mouse PCs in the zebrin-negative module, but not in the zebrin-positive module. AAV-mediated PKCγ re-expression in PKCγ-deficient mouse PCs in the zebrin-negative module restored the enhanced intrinsic excitability to a level comparable to that of wild-type mouse PCs. In parallel with higher intrinsic excitability, we found larger hyperpolarization-activated cyclic nucleotide-gated (HCN) channel currents in PKCγ-cKO PCs located in the zebrin-negative module, compared with those in WT mouse PCs in the same region. However, pharmacological inhibition of the HCN currents did not restore the enhanced intrinsic excitability in PKCγ-cKO PCs in the zebrinnegative module. These results suggested that PKCγ suppresses the intrinsic excitability in zebrinnegative PCs, which is likely independent of the HCN current inhibition.